2022
DOI: 10.3389/fimmu.2022.991291
|View full text |Cite
|
Sign up to set email alerts
|

Using personalized prognosis in the treatment of relapsing multiple sclerosis: A practical guide

Abstract: The clinical course of multiple sclerosis (MS) is highly variable among patients, thus creating important challenges for the neurologist to appropriately treat and monitor patient progress. Despite some patients having apparently similar symptom severity at MS disease onset, their prognoses may differ greatly. To this end, we believe that a proactive disposition on the part of the neurologist to identify prognostic “red flags” early in the disease course can lead to much better long-term outcomes for the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Although some publications regarding the impact of gender on the prognosis of MS suggest that the male gender is among the poor prognostic factors, other publications state that the impact of gender on prognosis is not significant 28,29 . In a study that included 1,074 men and 2,025 women, it was observed that there was no difference between the genders when looking at the progressive MS phenotype 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Although some publications regarding the impact of gender on the prognosis of MS suggest that the male gender is among the poor prognostic factors, other publications state that the impact of gender on prognosis is not significant 28,29 . In a study that included 1,074 men and 2,025 women, it was observed that there was no difference between the genders when looking at the progressive MS phenotype 30 .…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32] In the scientific literature, a number of recent peer-reviewed publications, including studies, reviews, and opinion pieces, recommend the use of the early high-efficacy treatment strategy, especially in patients with high disease activity. [33][34][35][36][37][38] In clinical practice, an increasing number of neurologists prefer the treatment strategy of initiating high-efficacy therapies early for the appropriate patients (instead of following the traditional escalation treatment strategy), according to the clinical experts consulted.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Moreover, patients with secondary or relapsed AML at the time of study initiation exhibited considerably impaired HRQoL compared to those with de novo AML [ 8 ]. It was found that changes in patients' quality of life were associated with long-term survival across various diseases, with diminished quality of life indicating a poor prognosis for patients [ [9] , [10] , [11] ]. Similarly, poor HRQoL at the time of patient diagnosis has been associated with reduced survival rates in cases of AML [ 12 ].…”
Section: Introductionmentioning
confidence: 99%